Nasal or throat sampling is adequate for the detection of the human respiratory syncytial virus in children with acute respiratory infections. Issue 9 (26th May 2019) - Nguyen, Van Hoan; Russell, Fiona M; Dance, David AB; Vilivong, Keoudomphone; Phommachan, Souphatsone; Syladeth, Chanthaphone; Lai, Jana; Lim, Ruth; Morpeth, Melinda; Mayxay, Mayfong; Newton, Paul N; De Lamballerie, Xavier; et al.
Abstract: Human respiratory syncytial virus (HRSV) is one of the most important causes of acute respiratory infections (ARI) in young children. HRSV diagnosis is based on the detection of the virus in respiratory specimens. Nasopharyngeal swabbing is considered the preferred method of sampling, although there is limited evidence of the superiority of nasopharyngeal swabs (NPS) over the less invasive nasal (NS) and throat (TS) swabs for virus detection by real‐time reverse transcription quantitative polymerase chain reaction (RT‐qPCR). In the current study, we compared the three swabbing methods for the detection of HRSV by RT‐qPCR in children hospitalized with ARI at Mahosot Hospital, Vientiane, Laos. In 2014, NS, NPS, and TS were collected from 288 children. All three samples were tested for HRSV by RT‐qPCR; 141 patients were found positive for at least one sample. Almost perfect agreements ( κ > 0.8) between the swabs, compared two by two, were observed. Detection rates for the three swabs (between 93% and 95%) were not significantly different, regardless of the clinical presentation. Our findings suggest that the uncomfortable and technically more demanding NPS method is not mandatory for HRSV detection by RT‐qPCR.